PHILOSOPHICAL REFLECTIONS ON ARTIFICIAL INTELLIGENCE: ETHICS, CONSCIOUSNESS, AND THE FUTURE OF HUMAN-MACHINE INTERACTION - Dr. Laila Rahman (Modern American Journals, 2025)
Artificial Intelligence (AI) has made profound strides in recent years, influencing every facet of human life—from healthcare and finance to transportation and entertainment. As AI becomes increasingly sophisticated, philosophical questions about its ethics, consciousness, and the potential for meaningful human-machine interaction become more pressing. This paper reflects on key philosophical debates surrounding AI, particularly focusing on ethical concerns, the concept of machine consciousness, and the implications of AI on human identity and societal structures. By examining the historical context of AI development, ethical frameworks such as utilitarianism and deontology, and contemporary debates about AI's role in the future, this paper aims to explore the broader implications of AI's integration into society. Ultimately, it proposes a critical engagement with AI that includes the development of ethical guidelines, greater transparency, and the recognition of the potential for human-machine collaboration in shaping a future where both coexist harmoniously.
Keywords: Artificial Intelligence, Ethics, Consciousness, Human-Machine Interaction, Technology, Philosophy, Machine Learning, Ethics of AI, Consciousness, Human Identity.